Forecasting of Socio-Economic Development of Regions in Kazakhstan: Principles, Features and Disadvantages - L. A. Balgarina; S. A. Jumabayev; Y. K. Shokamanov (Экономика: стратегия и практика)
The forecast is an important strategic document for planning and defining goals and priorities for the region’s development. Socio-economic forecasting is relevant all over the world. For this reason, the issues of formation and practical application of forecasts, including regional ones, are reflected in many research papers. The purpose of the study is to consider the process of developing a forecast of socio-economic development in the regions of Kazakhstan and to identify factors that worsen its quality. The authors used a combination of research methods: description, observation, content analysis and system-analytical. The description of the forecasting process was carried out in the Bizagi Model software package. The main sources of information of the study were the observation of the procedure for making a forecast of the region and the analysis of legal acts regulating the forecasting processes in the Republic of Kazakhstan. To achieve the purpose of the study, the role of forecasting in management was determined, the differences between the forecast and the plan, the primary methods and types of forecasting, approaches to forecasting were listed, the process of making a forecast at the regional level was described and analyzed, “weaknesses” in the forecast development procedure were identified. The result of the study was the identification of limitations affecting the quality and efficiency of the use of the developed forecasts, and ways to reduce them are proposed. The study contributes to understanding the regional forecasting process and the causes of problems arising during its development.